Seasonal variability of the quality of water sources and drilling artesian common Zagnanado and Zogbodomey in central Benin - LALEYE, GILBERT TITE; DOVONON, LEONCE FIRMIN COMLAN; AZONHE, THIERRY HERVE SETONDJI NICEPHORE; HOUSSOU, CHRISTOPHE SEGBE; EDORH, ALEODJRODO EDGARD PATRICK VINCENT (My University, 2015)
The basins of rivers Ouémé and Zou were selected to better understand the relationships between the waters of artesian springs and artesian water wells in the region Zagnanado and Zogbodomey. From physicochemical analyzes (temperature, pH, electrical conductivity, major cations and anions) on water samples taken from both the artesian springs and artesian wells, the chemical signature of each water system been established. The results show that drilling water has a relatively acidic pH. Against by the sources have a pH close to neutrality. Of the rainy season to the dry season, is observed dynamics of geochemical facies in the waters of artesian wells, while it remains unchanged for almost all water artesian springs. . The waters of artesian springs have a chemical signature similar to that of artesian wells with an overlay that varies according to climatic events and fracturing phenomena, which allow the rapid transport of water through the bedrock. This reflects the existence of favorable conditions to trade flows between the river system and the continuous aquifers.
Keywords: artesian water sources; water artesian wells; hydrochemistry; Zagnanado-Zogbodomey region